Substitutional boron and nitrogen pairs in diamond. A quantum mechanical vibrational analysis. (May 2019) - Salustro, Simone; Colasuonno, Fabio; Ferrari, Anna Maria; D'Amore, Maddalena; Mackrodt, William C.; Dovesi, Roberto
Abstract: The lattice structures, electronic characteristics and spectroscopic features of the three vicinal substitutional, spin zero defects, N s -N s (A-centre), B s -B s, and B s -N s in diamond are reported. They are derived from all-electron B3LYP calculations based on Gaussian basis sets, within a periodic supercell scheme, including both 64- and 216-atom cells. The local geometry reflects the differences between the strong C-C bond of the host lattice and the weaker impurity-impurity bonding in the defective systems. The band structures show two occupied bands 1.06 eV above the VBE for N s -N s, and empty bands 3.36 eV and 0.25 eV below the CBE for B s -B s and for B s -N s respectively. The IR spectra of B s -B s and N s -N s contain sharp peaks at 631 cm −1, 692 cm −1 and 1373 cm −1, and 451 cm −1, 571 cm −1 and 1276 cm −1, respectively, which might reasonably be considered as 'finger prints' for these systems. For B s -N s, a set of medium intensity absorptions are predicted at 890 cm −1, 945 cm −1, 1018 cm −1, 1078 cm −1 and 1281 cm −1 . However, numerous peaks in this region have been predicted for other defective systems, so that the firm identification of B s -N s based on these frequencies is much less certain than B s -B s and N s -N s . Graphical abstract: Image 1